The use of international agreements in transnational environmental protection - Finus, Michael; Cooper, Philip; Almer, Christian Alexander (Oxford economic papers, 2017)
Abstract. International environmental agreements (IEAs) offer a potent method for addressing environmental issues that transgress national borders, but realizi
Gesehen am 22.08.2019